2019
DOI: 10.1016/j.jhazmat.2018.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary pharmaceutical residues from natural water to tap water: Sales, occurrence and fate

Abstract: Veterinary pharmaceuticals (VPs) increasingly used in animal husbandry have led to their presence in aquatic environments -surface water (SW) or groundwater (GW) - and even in tap water. This review focuses on studies from 2007 to 2017. Sixty-eight different veterinary pharmaceutical residues (VPRs) have been quantified worldwide in natural waters at concentrations ranging from nanograms per liter (ng L) to several micrograms per liter (μg L). An extensive up-to-date on sales and tonnages of VPs worldwide has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 234 publications
(65 citation statements)
references
References 169 publications
(343 reference statements)
1
60
0
1
Order By: Relevance
“…Among the five metabolites investigated, three were detected (neospiramycin, triclabendazole sulfone, triclabendazole sulfoxide). Among the 17 VPRs quantified in water resources in this study, 11 have been previously found in natural waters at similar concentrations (florfenicol, flumequine, flunixin, levamisole, ivermectin, oxytetracycline, sulfadiazine, sulfamethazine, tilmicosin, trimethoprim, triclabendazole) (Charuaud et al, 2019;Sinclair et al, 2007). For example, sulfadiazine (from 508 ng/L to 2946 ng/L in this study) was quantified in surface water up to 2313 ng/L in the Llobregat River in Spain (Iglesias et al, 2014) and florfenicol (from 7 ng/L to 930 ng/L in this study) was quantified in South Korea up to 340 ng/L (Kim et al, 2016) and in China up to 930 ng/L (Zhou et al, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 67%
See 1 more Smart Citation
“…Among the five metabolites investigated, three were detected (neospiramycin, triclabendazole sulfone, triclabendazole sulfoxide). Among the 17 VPRs quantified in water resources in this study, 11 have been previously found in natural waters at similar concentrations (florfenicol, flumequine, flunixin, levamisole, ivermectin, oxytetracycline, sulfadiazine, sulfamethazine, tilmicosin, trimethoprim, triclabendazole) (Charuaud et al, 2019;Sinclair et al, 2007). For example, sulfadiazine (from 508 ng/L to 2946 ng/L in this study) was quantified in surface water up to 2313 ng/L in the Llobregat River in Spain (Iglesias et al, 2014) and florfenicol (from 7 ng/L to 930 ng/L in this study) was quantified in South Korea up to 340 ng/L (Kim et al, 2016) and in China up to 930 ng/L (Zhou et al, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…A C C E P T E D M A N U S C R I P T 4 al., 2010;Hu et al, 2014;Iglesias et al, 2014;Kim et al, 2016;Luo et al, 2011;Ok et al, 2011;Tong et al, 2014Tong et al, , 2009Wei et al, 2011;Yao et al, 2017Yao et al, , 2015Zhou et al, 2016). As data on VPR behavior in drinking water treatment plants (DWTPs) is scarce (Charuaud et al, 2019), there is a public health concern as the human population may be exposed to these compounds via tap water, especially when tap water is produced with surface water resources from intensive livestock areas. In Brittany, surface water is the major resource (75%) for water production; while the national ratio is 64% groundwater and 36% surface water (ARS Bretagne, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ads.% = (C 0 − C e )∕C 0 * 100 (2) wileyonlinelibrary.com/jctb where C 0 is the initial concentration of adsorbate (in mg L −1 ), C e is the residual concentration of adsorbate at equilibrium (in mg L −1 ), V is the volume of solution (in liters), and m is the mass of dry adsorbent (in grams).…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Nevertheless, the abuse of antibiotics in animal husbandry and the ineffective removal by conventional water treatment technologies have caused serious detriments to public health. Antibiotics of tetracyclines, fluoroquinolones and sulfonamides are frequently detected in surface waters in the ng to μg L −1 range of concentration . Their accumulation and persistence in aquatic environments can lead to the unbalance of the microbial ecosystem, the proliferation of antibiotic resistant pathogens and the inefficiency in treating infection .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation